MHD natural convection and entropy generation of non-Newtonian ferrofluid in a wavy enclosure. (15th May 2021) - Afsana, Sadia; Molla, Md. Mamun; Nag, Preetom; Saha, Litan Kumar; Siddiqa, Sadia
Highlights: MHD natural convection and entropy generation of non-Newtonian ferrofluid is investigated in a wavy cavity. Hartmann number attenuates the rate of heat transfer and convective flow within the enclosure. The addition of ferro-particle augments the heat transfer rate in shear-thickening cases. Rayleigh number is directly proportional to the average Nusselt number and total entropy. A new correlation for the average Nusselt number is proposed for the shear-thinning fluids. Graphical abstract: Abstract: Two-dimensional laminar magneto-hydrodynamic (MHD) natural convection flow of non-Newtonian ferrofluid has been investigated to understand the characteristics of heat transfer, streamlines, isotherms, and entropy generation in a wavy enclosure using the finite volume method (FVM). The horizontal boundaries of the cavity are assumed to be thermally adiabatic, while the temperatures of the left and right vertical walls are presumed to be T H and T C, respectively. The rheology of the nanofluid is represented through the power-law model, and the density variations due to thermal expansion lie within the framework of the Boussinesq approximation. Numerical simulations have been carried out for a range of dimensionless parameters such as Rayleigh number ( R a = 10 3, 10 4, 10 5 ), Hartmann number ( H a = 0, 10, 20 ), power-law index ( n = 0.6, 0.8, 1.0, 1.2, 1.4 ), volume fraction ( ϕ = 0, 0.05, 0.1 ), and Prandtl number P r = 6.8377. Results indicate that the isotherms of the shear-thinning fluid are dominated by thermal convection, whereas conduction is more pronounced for shear-thickening fluids. The average Nusselt number of the non-Newtonian ferrofluid increases with the attenuation of the Hartmann number and augmentation of the Rayleigh number, and in our entire simulation, the maximum value of N u ¯, due to the addition of ferro-particles, is found to be 8.07. The power-law index has a remarkable influence on the streamlines, and ψ m a x tends to decrease when n is increased gradually from shear-thinning to shear-thickening fluid behavior. Moreover, it is revealed that the heat transfer rate of ferrofluid ( ϕ =10%) increases up to 26% for the shear-thinning case and 25% for the shear-thickening case, under the influence of the magnetic field. Further, it is inferred that the irreversibility due to heat transfer, fluid friction, and magnetic field for the shear-thinning, Newtonian and shear-thickening ferrofluids, can be minimized based on the optimal parametric combination. The increment of Hartmann number results in 60% attenuation of total entropy for shear-thinning fluid and 9% diminution for the shear-thickening case. With the augmentation of the power-law index, the entropy generation is found to decrease by 80% in the absence of the magnetic field effect and by 54% in the presence of it. A new correlation for the average Nusselt number is proposed for the shear-thinning fluids and shows a good agreement between the computed and predicted results.